Recovery from supercooling, freezing, and cryopreservation stress in larvae of the drosophilid fly, Chymomyza costata - Štětina, Tomáš; Hůla, Petr; Moos, Martin; Šimek, Petr; Šmilauer, Petr; Koštál, Vladimír (Scientific reports, 2018)
Physiological adjustments accompanying insect cold acclimation prior to cold stress have been relatively well explored. In contrast, recovery from cold stress received much less attention. Here we report on recovery of drosophilid fly larvae (Chymomyza costata) from three different levels of cold stress: supercooling to -10 °C, freezing at -30 °C, and cryopreservation at -196 °C. Analysis of larval CO2 production suggested that recovery from all three cold stresses requires access to additional energy reserves to support cold-injury repair processes. Metabolomic profiling (targeting 41 metabolites using mass spectrometry) and custom microarray analysis (targeting 1,124 candidate mRNA sequences) indicated that additional energy was needed to: clear by-products of anaerobic metabolism, deal with oxidative stress, re-fold partially denatured proteins, and remove damaged proteins, complexes and/or organelles. Metabolomic and transcriptomic recovery profiles were closely similar in supercooled and frozen larvae, most of which successfully repaired the cold injury and metamorphosed into adults. In contrast, the majority of cryopreseved larvae failed to proceed in ontogenesis, showed specific metabolic perturbations suggesting impaired mitochondrial function, and failed to up-regulate a set of 116 specific genes potentially linked to repair of cold injury.
Keywords: kryoprezervace; fyziologický stres; zmrazování; Cryopreservation; Preservation, Biological; Metabolomics; reakce na chladový šok; Freezing; larva; metabolomika; zvířata; Cold-Shock Response; Stress, Physiological; stanovení celkové genové exprese; ochrana biologická; Larva; Animals; Gene Expression Profiling; Drosophilidae